Biopolymer production in bio electrochemical system: Literature survey. (September 2019) - Banu, J. Rajesh; Kumar, M. Dinesh; Gunasekaran, M.; Kumar, Gopalakrishnan
Abstract: Bio-electrochemical systems (BESs) are the bacterial systems which are utilized to harvest electricity directly by treating waste or wastewater together with production of valuable chemicals such as biopolymer, various alcohols, acetate, butyrate and also generation of biogas such as CH4 and H2 . Biopolymers are vital substitutes for the petroleum-based plastics due to environment friendly manufacturing methods, biocompatibility and biodegradability. Biopolymers are biodegradable components which are produced from renewable resources by using microorganisms as intracellular carbon and energy storage compounds. In this review, a detailed analysis of various bio-electrochemical systems was explained. This review also provides a discussion about biopolymer production in various bio-electrochemical systems. Highlights: BES – dual function as simultaneous wastewater treatment and PHA generation Biodegradable polymers are future environmental friendly plastics. In BES, biopolymers produced under microaerophilic environment at biocathode.